Spontaneous Intraventricular Hemorrhage Caused by Sphenoid Meningioma - Mandour, Cherkaoui; Laaguili, Jawad; Gazzaz, Miloudi; Mostarchid, Brahim el (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Introduction Benign sphenoid meningioma presenting with an acute intraventricular hemorrhage is extremely uncommon.Case report We report a case of a 61-year-old man who was admitted after sudden onset of a severe headache. Brain computed tomography revealed a sphenoid meningioma with acute intraventricular hemorrhage.Discussion Intraventricular hemorrhage caused by Meningiomas is infrequent. Several hypotheses have been proposed to explain the cause of hemorrhage.Conclusion The benignity of meningiomas is relative because these tumors can cause exceptional complications such as bleeding.
Keywords: hemorrhage; intraventricular; meningioma; sphenoid